2021
DOI: 10.1038/s41597-021-01022-6
|View full text |Cite
|
Sign up to set email alerts
|

Materials informatics platform with three dimensional structures, workflow and thermoelectric applications

Abstract: Since the proposal of the “Materials Genome Initiative”, several material databases have emerged and advanced many materials fields. In this work, we present the Materials Informatics Platform with Three-Dimensional Structures (MIP-3d). More than 80,000 structural entries, mainly from the inorganic crystal structural database, are included in MIP-3d. Density functional theory calculations are carried out for over 30,000 entries in the database, which contain the relaxed crystal structures, density of states, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…They calculated the median, mean, minimum, and maximum T g values of the 75 samples with multiple reported T g to create 4 datasets for training models. After the models construction with GPR, 4 metrics of 1‐R, [ 2 ] RMSE, average GPR‐uncertainty, and GPR noise‐hyperparameter were applied to evaluate the performance of the models (Figure 6d). The metrics revealed that the model constructed with median value dataset performed best with lower errors.…”
Section: Recent Progress Of Machine Learning In Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…They calculated the median, mean, minimum, and maximum T g values of the 75 samples with multiple reported T g to create 4 datasets for training models. After the models construction with GPR, 4 metrics of 1‐R, [ 2 ] RMSE, average GPR‐uncertainty, and GPR noise‐hyperparameter were applied to evaluate the performance of the models (Figure 6d). The metrics revealed that the model constructed with median value dataset performed best with lower errors.…”
Section: Recent Progress Of Machine Learning In Polymersmentioning
confidence: 99%
“…[ 104 ] Copyright 2021, American Chemistry Society. d) Comparison of the four models from four different datasets using metrics 1‐R, [ 2 ] RMSE, average GPR uncertainty and GPR noise‐parameters. Reproduced with permission.…”
Section: Recent Progress Of Machine Learning In Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their accuracy has always been questioned. In 2018, Xi et al (2018) screened chalcogenides with a diamond-like structure, space group 225, from the MatHub-3d database (Yao et al, 2021) through HTP calculations (Figure 5A). This work reported a new strategy for computing the electronic relaxation time τ, which was efficient enough for HTP calculation and more accurate than the more advanced electron-phonon coupling method.…”
Section: Diamond-like Compoundsmentioning
confidence: 99%
“…cnic.cn) is a Chinese HTP platform, which is a computational materials platform where users can perform online job setup, job submission, and monitoring via a web browser (Yang et al, 2018). The Materials Hub with three-dimensional structures (MatHub-3d, www.mathub3d.net, formerly MIP-3d) is a HTP platform developed by the MGI of Shanghai University, and focuses on energy, electronic structures, and electrical transport properties (Yao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%